2009
DOI: 10.1519/jsc.0b013e3181b073a8
|View full text |Cite
|
Sign up to set email alerts
|

Apnea Training Effects on Swimming Coordination

Abstract: Triathletes and elite breath-hold divers show an adaptive response to hypoxia induced by repeated epochs of breath holding. We hypothesized that hypoxic training could also improve swimming coordination. Before and after a 3-month breath-hold training program, 4 male swimmers performed a maximal incremental test on bicycle and a 50-m front crawl race at maximal speed without breathing so that interarm coordination could be assessed. Swim velocity, stroke rate (SR), stroke length (SL), and the arm stroke phases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 17 publications
3
21
1
Order By: Relevance
“…These results are consistent with the findings of the current study considering that the participants of the present study were untrained breath hold subjects. In contrast to the current study, Lemaitre et al determined an enhanced maximal and submaximal swimming performance after long-term apnea exercises because of the improved M axvo2 [31]. It means that apnea during several weeks of training may enhance performance.…”
Section: Discussioncontrasting
confidence: 89%
“…These results are consistent with the findings of the current study considering that the participants of the present study were untrained breath hold subjects. In contrast to the current study, Lemaitre et al determined an enhanced maximal and submaximal swimming performance after long-term apnea exercises because of the improved M axvo2 [31]. It means that apnea during several weeks of training may enhance performance.…”
Section: Discussioncontrasting
confidence: 89%
“…Moreover, there are some similarities between our data and those reported by authors who studied the effects of SS training in blood lactate levels, who found a significant decrease in La peak along a season [6], [7]. Training practice seems to produce such adaptations improving effectiveness at both peak and submaximal exercise [55], and could explain the improvements in work economy by promoting greater technique skills.…”
Section: Discussionsupporting
confidence: 86%
“…5–6 h a day, 6 days a week for 6 months) sufficiently stimulates EPO increase, which causes higher red blood cells concentration and greater abilities to hold one’s breath for longer periods of time (Lemaître, 2009). Delay in arterial blood O 2 desaturation development, preventing the most important organs from functioning during multiple breath-hold dives, leads to the conclusion that these actions may enhance diving reflexes, by enhancing O 2 management processes (Vasar and Kingisepp, 1980).…”
Section: The Role Of Training In the Development Of Diving Reflexes Imentioning
confidence: 99%